ANALYSIS OF PRODUCTION COST STRUCTURE AND BUSINESS INCOME SALT BUSINESS IN PADEMAWU SUB-DISTRICT, PAMEKASAN DISTRICT - Indah Septi Maulinda; Prasetyo Nugroho (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
The purpose of this research is to find out: 1) To determine the production costs in the salt business in Pademawu District, Pamekasan Regency. 2) To determine the level of income of the salt business in Pademawu District, Pamekasan Regency. In this study the authors used a quantitative approach. The population in this study were salt farmers in Pademwau District. The sample used in this study was 50 respondents of salt farmers in Pademawu District. Researchers collected data by means of field observations, interviews and distributing questionnaires. The results of this study indicate that: 1) The cost structure in the salt business is 37.24% variable costs or Rp14,544,200 and 62.76% fixed costs or Rp24,509,440. 2) The income received by salt farmers amounted to Rp133,932,360 with revenue of Rp172,986,000 minus total costs of Rp39,053,640. The conclusion from the results of research that has been done by the author is that the expenditure of salt farmers is greatest at fixed costs